CHRONOTHERAPY OF HYPERTENSION: LITERATURE REVIEW - Petrenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Review devoted to chronotherapy of hypertension. The questions of chronomedicine and chronobiology, biological rhythms, especially circadian regulation of blood pressure, types of daily blood pressure profile violations, the role of de-synchronization of biological rhythms in the development and course hypertension, opportunities to optimize antihypertensive therapy with the method of chronotherapy using alpha- and beta-blockers, angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, diuretics, calcium channel blockers and melatonin are contemplated.